Cognitive Decline Influences Emotional Creativity in the Elderly. Issue 1 (2nd January 2019) - Trnka, Radek; Cabelkova, Inna; Kuška, Martin; Nikolai, Tomas
Abstract : Little is known about the relationship between emotional creativity and age-related cognitive decline. This study explored how deficits in some cognitive abilities are related to emotional creativity, i.e., cognitive abilities relating to originality and appropriateness in emotional experience. One hundred and eighty-seven older adults (mean age = 63.2; 58.4% females) were administered the Emotional Creativity Inventory, the Frontal Systems Behavior Scale, and the Cognitive Complaint Interview. As hypothesized, emotional creativity was negatively related to apathy and positively to disinhibition/emotional dysregulation. Several processes, such as apathy-related loss of interest, unconcern, subjective lack of energy, and changed perception of one's disinhibited emotional reactions, may explain the observed results.